Education Financing Policy Controversy: Between Accessibility And Quality - Lu’at Happyana; Rahma Nanda Nur Azizah; Nur Anim Jauhariyah (STAI AN-NAJAH INDONESIA MANDIRI, 2024)
ABSTRACT Education financing policies face a dilemma between accessibility and quality. Affordable education increases accessibility but often compromises quality, while high-quality education requires significant investment that is less accessible. This study examines the dynamics of education financing policies at MTs YPI Darul Huda, Palembang, using a qualitative case study approach. Data were collected through interviews and participatory observation. The results show that programs like BOS and scholarships enhance educational access, yet challenges such as misallocation of funds and lack of transparency hinder their effectiveness. Effective policies should integrate accessibility and quality through needs-based allocation, transparency, and efficient management. Such policies can enhance students' motivation, participation, and contribute to the development of competitive human resources. Keywords: Accessibility, Quality, Financing of Education